2005
DOI: 10.1021/jm050144u
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Biological Activities of Disaccharide Daunorubicins

Abstract: Carbohydrate moiety is found in many anticancer nature products. To explore the carbohydrate moiety of daunorubicin in enhancing anticancer efficacy, several daunorubicin derivatives bearing disaccharide (1-8) have been synthesized. Their cytotoxicities were tested in leukemia K562 and colon cancer SW620 cells. Topoisomerase II (topo II) poisoning was performed with the in vivo complex of topoisomerase bioassay. In both cell lines, compounds with various terminal 2,6-dideoxy sugars (compounds 1, 3, 5, and 8) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…These analogs were tested to overcome P-gp binding by molecular modeling, cytotoxicity, and P-gp inhibition. Indeed, we have generated several lead compounds that maintain the anticancer activity and avert P-gp binding [23]. In addition, our results have also been confirmed by previous studies.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These analogs were tested to overcome P-gp binding by molecular modeling, cytotoxicity, and P-gp inhibition. Indeed, we have generated several lead compounds that maintain the anticancer activity and avert P-gp binding [23]. In addition, our results have also been confirmed by previous studies.…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown that modifying the sugar moiety in daunorubicin can change the anticancer efficacy of anthracyclines [21][22][23]. In addition, the 3'-amino group in the sugar may also play a role for P-gp recognition [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there have been intensive attempts to develop analogs with an improved therapeutic index. In the last 50 y, most modifications have been focused on the sugar moiety, providing a successful drug, epirubicin, as well as several promising candidates under clinical trials (1,2). In contrast, only a few analogs have been generated by altering the anthracycline core, most of which were obtained by chemical synthesis.…”
mentioning
confidence: 99%
“…Some 6-deoxy sugars form structural components of a variety of natural products, including antibiotics, 7,8) antifungals, 9) and anticancer agents. [10][11][12] These sugars generally participate in the molecular recognition of cellular targets by active compounds. 13) 6-Deoxy-L-galactose (L-fucose) is known as a major component of fucoidan from brown seaweed.…”
mentioning
confidence: 99%